Effects of Visual Separation and Physical Discontinuities when Distributing Information across Multiple Displays - Tan, Desney; Czerwinski, Mary (Human-Computer Interaction–INTERACT '03, 2003)
Systems that include multiple integrated displays distributed throughout the working environment are becoming prevalent. Compared to traditional desktop displays, information presented on such systems is typically separated at much wider visual angles. Additionally, since displays are often placed at different depths or are framed by physical bezels, they introduce physical discontinuities in the presentation of information. In this paper, we describe a study that utilizes a divided attention paradigm to explore the effects of visual separation and physical discontinuities when distributing information across multiple displays. Results show reliable, though small, detrimental effects when information is separated within the visual field, but only when coupled with an offset in depth. Surprisingly, physical discontinuities such as monitor bezels and even separation in depth alone do not seem to affect performance on the set of tasks tested. Following the findings, we provide recommendations for the design of hardware and software in multiple display environments.